If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 12 = 8x + -10 Reorder the terms: 12 + 9x = 8x + -10 Reorder the terms: 12 + 9x = -10 + 8x Solving 12 + 9x = -10 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 12 + 9x + -8x = -10 + 8x + -8x Combine like terms: 9x + -8x = 1x 12 + 1x = -10 + 8x + -8x Combine like terms: 8x + -8x = 0 12 + 1x = -10 + 0 12 + 1x = -10 Add '-12' to each side of the equation. 12 + -12 + 1x = -10 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = -10 + -12 1x = -10 + -12 Combine like terms: -10 + -12 = -22 1x = -22 Divide each side by '1'. x = -22 Simplifying x = -22
| 14x^2+4x= | | x-3+12=134 | | 3g+4n=18 | | v/8+2 | | 2x+4.1=x+1.1 | | n=9200ln(5(3)+3) | | 5/4x5/3(2+10) | | 2n+8=8 | | 8(x-3)=4x+-8 | | 4x^2-6x-56=3x-16 | | 4/5y-9=-1 | | 4a+3=56 | | 2/2/3x8 | | 15+h=-15 | | 4x-7(x-2)= | | 8x+11/9=-5 | | log(2x-8)-log(6x)=2 | | x^3+10x^2+9x=0 | | 22/3x8 | | 7+9n=79 | | 20x^3+60x^2+25x=0 | | 3x^2+7+8=6 | | c=-5c+-30 | | 3x^2+7+18=6 | | 3/4x-1/3=-8 | | d/-7=-4 | | 2x/6=-10 | | -p^2+p=18 | | 8k-5k=15 | | x^2+56x-406.25=0 | | 3x/9=-9 | | 5X+(-20)=65 |